A Web-Based Self-Management Intervention for Veterans With Chronic Conditions and Their Caregivers: A Pilot Study. (17th December 2021) - Trivedi, Ranak; Plummer, Katherine; Suresh, Madhuvanthi; Risbud, Rashmi; Humber, Marika; Zulman, Donna; Timko, Christine; Piette, John
Abstract: Web-based Self-management Using Collaborative Coping Enhancement in Diseases (Web-SUCCEED) is a dyadic intervention for patients and their caregivers designed to improve self-management through improving dyadic stress coping, dyadic relationships, and positive emotions. Veterans Affairs (VA) patients with one or more chronic conditions and positive screen for self-management distress were recruited with their informal caregiver from VA Palo Alto. Of the 17 patients and 16 caregivers recruited (62.3% of eligible), 8 patients and 8 caregivers (48.5%) completed the intervention and assessments. Twelve participants withdrew mostly citing the stress of the pandemic as their reason; 5 did not respond to multiple outreach efforts. Veterans were 66□18 y and caregivers were 58□16 y. Veterans and caregivers who completed the program rated it high on usability and acceptability. Pre-post t-tests across a psychosocial battery did not reveal significant differences; results were limited by incomplete post-intervention data. Further testing with modified retention strategies is recommended.